Munchausen Syndrome by Proxy in the Main Character of Dianne Sherman in Aneesh Chaganty’s Run (2020) - Nurhaliza Anggraini; Latifah Dwi Ariyani (Metaphor, 2024)
This study aims at analyzing the representation of Munchausen Syndrome by Proxy in Aneesh Chaganty’s Run, and the mental condition of the charachter who suffers from Munchausen Syndrome by Proxy in Aneesh Chaganty’s Run (2020). The method used in this research is qualitative approach. The object of this study is Aneesh Chaganty’s Run and the subject of this study is the dialogues between the characters and action pictures in Aneesh Chaganty’s Run. In collecting data, the techniques applied by the researcher are watching, reading, identifying, classifying, and selecting. To analyze the data, the researcher uses Munchausen Syndrome by Proxy study and Johari window’s theory of psychology. It is done through some steps as displaying, explaining, and interpreting. The result of this research shows that: first, the representations of Munchausen Syndrome by Proxy in the main character who suffers from Munchausen Syndrome by Proxy exists in this study. Those are; Striving to appear self-sacrificing and devoted, inducing symptom to her child, concerned about child’s health, being very knowledgeable about medical stuff, switch doctors and medical staff, falsifying diseases symptom. Second, the mental condition of the charachter who suffers from Munchausen Syndrome by Proxy reflect a balance and wholeness of her personality. It is described through 3 points, those are; manipulative behaviour, maladaptive daydreaming behaviour, and suffered from depression.